2012
DOI: 10.1088/0967-3334/34/1/17
|View full text |Cite
|
Sign up to set email alerts
|

K-nearest-neighbor conditional entropy approach for the assessment of the short-term complexity of cardiovascular control

Abstract: Complexity analysis of short-term cardiovascular control is traditionally performed using entropy-based approaches including corrective terms or strategies to cope with the loss of reliability of conditional distributions with pattern length. This study proposes a new approach aiming at the estimation of conditional entropy (CE) from short data segments (about 250 samples) based on the k-nearest-neighbor technique. The main advantages are: (i) the control of the loss of reliability of the conditional distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 23 publications
2
49
0
2
Order By: Relevance
“…The decrease of entropy as a consequence of the sympathetic activation during orthostatic challenge was also shown by Turianikova et al [36]. On the other hand, pharmacological autonomic blockade with atropine, as well as propranolol combined with atropine have also decreased heart entropy, suggesting that vagal activity is the main modulator of heart rate complexity [37]. A recent study by Weipert [38] indicates that both vagal and sympathetic modulations contribute to heart rate complexity, and what is more, different autonomic states might result in the same value of SampEn (e.g., reciprocal changes of vagal and sympathetic systems and co-activation of both systems).…”
Section: Neg Vs Vvs_2 Groupssupporting
confidence: 52%
“…The decrease of entropy as a consequence of the sympathetic activation during orthostatic challenge was also shown by Turianikova et al [36]. On the other hand, pharmacological autonomic blockade with atropine, as well as propranolol combined with atropine have also decreased heart entropy, suggesting that vagal activity is the main modulator of heart rate complexity [37]. A recent study by Weipert [38] indicates that both vagal and sympathetic modulations contribute to heart rate complexity, and what is more, different autonomic states might result in the same value of SampEn (e.g., reciprocal changes of vagal and sympathetic systems and co-activation of both systems).…”
Section: Neg Vs Vvs_2 Groupssupporting
confidence: 52%
“…After one of the first attempts to elucidate the autonomic influence on HR entropy during autonomic blocking and exercise, Tulppo et al concluded that sympathetic rather than vagal efferent activity modulates HR complexity [68]. In a recent experiment the group around Porta used refined methods to estimate HR complexity and an autonomic blocking protocol to elucidate the underlying autonomic mechanisms [22]. From their results the authors concluded that vagal efferent activity is the main contributor, because high dose of atropine significantly reduced complexity compared to baseline conditions, while sympathetic blocking with propranolol did not have any effect on HR complexity.…”
Section: Discussionmentioning
confidence: 99%
“…However, many researchers found at least modest correlations for some nonlinear measures and traditional HRV indices under different conditions [5,9,19,20]. It has also been shown that complexity of short-term HRV is under control of the autonomic nervous system [21,22]. Currently, there are only few studies available that compared the cardiovascular response pattern to different exercise modes at similar HR.…”
Section: Introductionmentioning
confidence: 99%
“…In another words, complexity is different from irregularity. Similar paradox also appears in other entropies such as fuzzy entropy (FuzzyEn) [14], permutation entropy [15], and conditional entropy [16]. The paradox may be due to the fact that conventional entropies fail to account for the multiple time scales inherent in healthy physiologic dynamics.…”
Section: Introductionmentioning
confidence: 93%